2011
DOI: 10.1007/s00217-011-1531-8
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, physical and sensory quality of ice-stored Atlantic cod (Gadus morhua) as affected by pre-slaughter stress, percussion stunning and AQUI-S™ anaesthesia

Abstract: Biochemical, physical and sensory quality of farmed Atlantic cod subjected to percussion stunning (control), anaesthesia (AQUI-S TM ) and excessive exercise (30 min chasing before slaughter, 'stressed') were analysed after 7 days of ice storage. The white muscle energy status (initial pH, muscle twitches and high-energy phosphates) revealed that the fish were truly representatives of rested (percussion stunned and anaesthetised) and stressed cod. Sensory evaluation showed that the fillets of cod exposed to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
2
33
1
3
Order By: Relevance
“…For some species, it appears to be a good method, since the method anesthetizes the animal preslaughter and therefore decreases pain sensitivity (Acerete et al, 2009;Giuffrida et al, 2007). For other species, it has been reported that CO 2 gas causes discomfort such as agony and escape attempt (Erikson, 2011;Roth, Moeller, Veland, Imsland, & Slinde, 2002). Therefore, further species-specific studies on stress responses and meat quality of fish induced by this stunning method are needed.…”
Section: Introductionmentioning
confidence: 94%
“…For some species, it appears to be a good method, since the method anesthetizes the animal preslaughter and therefore decreases pain sensitivity (Acerete et al, 2009;Giuffrida et al, 2007). For other species, it has been reported that CO 2 gas causes discomfort such as agony and escape attempt (Erikson, 2011;Roth, Moeller, Veland, Imsland, & Slinde, 2002). Therefore, further species-specific studies on stress responses and meat quality of fish induced by this stunning method are needed.…”
Section: Introductionmentioning
confidence: 94%
“…Vários autores afirmam que o estresse sofrido antes do abate acelera a entrada do rigor mortis (SIGHOLT et al, 1997;THOMAS et al, 1999;KRISTOFFERSEN et al, 2006;PEDRAZANI et al, 2007;RIBAS et al, 2007;DIGRE et al, 2011;ERIKSON et al, 2012). Os peixes que são submetidos ao estresse pré-abate gastam suas reservas energéticas durante determinado estímulo ambiental adverso ao equilíbrio fisiológico dos animais.…”
Section: Resultsunclassified
“…The fillet hardness values were then around 10 N (Table 5). Other reported hardness values of fillets cut from farmed cod stored on ice for 7 or 8 days, obtained by use of the same instrumental method, are 11-14 N (Digre et al, 2011a(Digre et al, , 2011bErikson et al, 2012), 5-6 N (Erikson et al, 2011), and 12-17 N (Digre et al, 2010. Hardness values measured after ice storage were discarded because instrument set points were accidentally not stored.…”
Section: Hardnessmentioning
confidence: 91%
“…The corresponding K-values were about 50% (Erikson et al, 2011). In another study, the K-values after 7 days on ice were 53-68% (Digre et al, 2011b). Degradation of glycogen occurs during freezing along with synthesis and degradation of A TP.…”
mentioning
confidence: 85%